Exploring nurses’ attitudes toward geriatric care: A qualitative study - Criestina, Mari; Santos, Jose Antonio (Indonesian Journal of Health Services, 2025)
Background: The ageing population worldwide has created increasing demands on healthcare systems, particularly in low- and middle-income countries where geriatric services are underdeveloped. Nurses play a pivotal role in caring for older adults, yet their attitudes and preparedness remain inconsistent due to limited training, systemic constraints, and emotional challenges. Objective: This study aimed to explore nurses’ attitudes toward geriatric care and to identify the factors that influence their perceptions and practices. Methods: A qualitative descriptive exploratory design was employed in selected hospitals providing adult and geriatric care. Eighteen nurses were recruited using purposive sampling, with inclusion criteria of at least one year of clinical experience and direct involvement in elderly care. Data were collected through semi-structured, in-depth interviews and analyzed using thematic analysis. Trustworthiness was ensured through member checking, peer debriefing, and an audit trail. Results: Four major themes emerged: perceptions of ageing and older adults, professional challenges in care delivery, emotional and relational dimensions of care, and opportunities for improvement in geriatric nursing practice. Nurses demonstrated empathy and respect toward older adults but faced barriers such as high workload, limited gerontological training, communication difficulties, and lack of institutional support. Despite these challenges, participants described meaningful relationships and rewarding experiences that reinforced their professional commitment. Conclusion: Nurses’ attitudes toward geriatric care are shaped by a balance between compassion and systemic limitations. Positive attitudes were linked to personal values and cultural respect for elders, while negative experiences stemmed from institutional gaps and insufficient preparedness. Strengthening gerontological education, providing continuous professional development, enhancing institutional support, and prioritizing geriatric services in health policy are essential to foster positive professional attitudes and ensure quality care for ageing populations.